Primary transitional cell carcinoma of bulbar urethra (Indian Journal of Case Reports, 2018)
Primary urethral carcinoma (UC) is a rare entity, and bulbar UCs of transitional cell origin are even rarer. Primary presentation as a scrotal abscess and urethrocutaneous fistula is rarely documented in UC patients. We present a case of a 66-year-old male presenting to emergency department with a scrotal abscess. Following blind incision and drainage, the urethral injury was suspected, and biopsy of suspicious lesion was taken from scrotum which came out to be invasive transitional cell carcinoma. A wide local excision of the tumor was done after workup. Hence, all patients with scrotal abscess and urethrocutaneous fistula should be investigated before performing any blind procedure.